2012
DOI: 10.1002/jtr.1926
|View full text |Cite
|
Sign up to set email alerts
|

Hungry for Growth? Small and Medium‐sized Tourism Enterprise (SMTE) Business Ambitions, Knowledge Acquisition and Industry Engagement

Abstract: Differences are identified between the preferred information and learning channels of small and medium-sized tourism enterprise (SMTE) proprietors, who have an interest in business operations (growers) or who have relatively less interest (lifestylers). Lifestylers sign up frequently to tourism industry associations, whereas growers have a tendency to join generic business groupings. The most common information for both groups is marketing related, and intensive use is made of online information to support day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Related concepts been used to interrogate small and medium sized enterprises (SMEs) as well as larger organisations (Fogg, 2012;Harris, McAdam, McCausland and Reid, 2013;Tejada and Moreno, 2013). Further, there is emerging evidence that tourism enterprises are particularly dependent on external knowledge, such as that which may be gleaned from suppliers, especially when compared with businesses in other sectors (Williams and Shaw, 2011;King, Breen and Whitelaw, 2012). Following the development of a validated instrument for its measurement, this paper reports the findings of a survey into levels of absorptive capacity within the British hotel sector and considers the implications of the findings for how absorptive capacity should be theorised in tourism.…”
Section: Introductionmentioning
confidence: 99%
“…Related concepts been used to interrogate small and medium sized enterprises (SMEs) as well as larger organisations (Fogg, 2012;Harris, McAdam, McCausland and Reid, 2013;Tejada and Moreno, 2013). Further, there is emerging evidence that tourism enterprises are particularly dependent on external knowledge, such as that which may be gleaned from suppliers, especially when compared with businesses in other sectors (Williams and Shaw, 2011;King, Breen and Whitelaw, 2012). Following the development of a validated instrument for its measurement, this paper reports the findings of a survey into levels of absorptive capacity within the British hotel sector and considers the implications of the findings for how absorptive capacity should be theorised in tourism.…”
Section: Introductionmentioning
confidence: 99%
“…Existing research has identified a number of information sources used by micro/SME firms, such as the internet, personal networks, the media, external professionals (consultants, accountants) and trade associations (Bennett and Ramsden, 2007;Bennett and Robson, 1999b;King, Breen and Whitelaw, 2014;Peck et al, 2012). Existing research has identified a number of information sources used by micro/SME firms, such as the internet, personal networks, the media, external professionals (consultants, accountants) and trade associations (Bennett and Ramsden, 2007;Bennett and Robson, 1999b;King, Breen and Whitelaw, 2014;Peck et al, 2012).…”
Section: Source Of Knowledgementioning
confidence: 99%
“…Tourism Small and Medium Enterprises (TSMEs) performance and survival in the industry are particularly important to Malaysia because apart from their key role in delivering tourism products to the tourist, they also play an active role in advancing the local community (King et al, 2014;Set, 2013). It is essential to observe TSMEs performance to ensure TSMEs reach their full potential.…”
Section: *Thementioning
confidence: 99%